2008
DOI: 10.1080/07418820801930118
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gun Acquisition, Carrying, and Use Among Juvenile and Adult Arrestees: Evidence from a High‐Crime City

Abstract: Researchers continue to examine the macrolevel trends of gun crime but little consensus exists regarding the microlevel determinants of gun behaviors. Moreover, little is known if patterns of gun behavior vary between adults and juveniles. This research examines patterns of gun possession, carrying, and use across adult and juvenile arrestees. This research moves beyond descriptive studies of aggregate gun patterns and explores the demographic and perceptual correlates that may inhibit or facilitate gun behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 56 publications
4
52
0
1
Order By: Relevance
“…First, evidence suggests that violent crime is a predictor of legal gun ownership (Bordua & Lizotte, 1979;Kleck & Kovandzic, 2009) and legal handgun purchases (McDowall & Loftin, 1983). Moreover, fear of victimization has been linked to legal gun ownership within an individual's home (Miethe, 1995;Warr & Ellison, 2000) as well as carrying an illegal gun in public for purposes of self-protection (Bankston & Thompson, 1989;Vacha & McLaughlin, 2000;Watkins et al, 2008). Thus, it seems reasonable to assume violent crime could predict legal concealed firearm carrying.…”
Section: Introductionmentioning
confidence: 99%
“…First, evidence suggests that violent crime is a predictor of legal gun ownership (Bordua & Lizotte, 1979;Kleck & Kovandzic, 2009) and legal handgun purchases (McDowall & Loftin, 1983). Moreover, fear of victimization has been linked to legal gun ownership within an individual's home (Miethe, 1995;Warr & Ellison, 2000) as well as carrying an illegal gun in public for purposes of self-protection (Bankston & Thompson, 1989;Vacha & McLaughlin, 2000;Watkins et al, 2008). Thus, it seems reasonable to assume violent crime could predict legal concealed firearm carrying.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, gun carrying was the only individual criminality factor that was impacted by the gang's behaviors. Watkins, Huebner, and Decker (2008) explored whether gun possession, frequency of gun carrying, and actually firing the gun were impacted by an individual's membership within a gang. The results indicated that gang membership was the strongest of ten predictors of gun carrying (Watkins et al, 2008).…”
Section: Gang Membership and Gun Carryingmentioning
confidence: 99%
“…The relationship between offenders and victims [4,40] could not be tested. And it was impossible to analyze differences between male and female offenders [4], gang membership [5][6][7], and attitudes and mental health conditions of the offenders [22,[41][42][43].…”
Section: Discussion Of Related Issuesmentioning
confidence: 99%
“…Individual characteristics that are found to influence gun crimes include race [1,2], age [3,4], sex, gang membership [5][6][7], drug involvement, and juvenile and adult status [5,[7][8][9][10][11][12][13][14][15]. Gun crimes range from illegal possession [16,17], unlawfully receiving or transferring a firearm [18], to violent crimes such as robbery and homicide [17,19].…”
Section: Establishing a Conceptual Frameworkmentioning
confidence: 99%